Development and validation of a mass spectrometry-based assay for quantification of insulin-like factor 3 in human serum - Anand-Ivell, Ravinder; Juul, Anders; Albrethsen, Jacob (Walter de Gruyter, 2018)
BACKGROUND: The circulating level of the peptide hormone insulin-like factor 3 (INSL3) is a promising diagnostic marker reflecting Leydig cell function in the male. Few commercial immunoassays of varying quality exist. Therefore, we decided to develop and validate a precise method for quantification of INSL3 by mass spectrometry.